LOCAL KNOWLEDGE: THE HUMAN CAPITAL FOR COPING WITH CRISIS GENERATED BY ECONOMIC BLOCKADE - Kumar, Santosh (PEOPLE: International Journal of Social Sciences, 2017)
To analyze how local knowledge helped people to cope with the crisis occurred by economic blockade in Nepal for a five months long (from September 2015 to January 2016) is the purpose of this paper. The incidence of economic blockaded is not only seen in Nepal but also in the world. Actually, economical blockade is the imposition of power used by a country over another country to influence socioeconomic status for their economic benefits, achieving moral or ethical goals. It generally blocks the supply of fuel and medicine along with other essential commodities to a landlocked country. It is the unnecessary power imposition by any country or state to another that violates the basic right (education, health, social security, food, energy and transportation) of people. Furthermore, it creates an additional burden to the people in their daily life. There are various modes of economic blockade exists. Generally, obstruction of economic resources, control over trade, withdrawn of business and deferment of assistance are adopted by the country in terms of the blockade. However, control over trade is taken as very effective one and India adopted it over Nepal due to the dissatisfaction over the newly formed constitution in Nepal. In a condition, people motivated to identify locally available resources and utilize its maximum. They used their local knowledge (the human capital) and creativity with confidence that helps them to cope with the crisis and made them self-reliant.